Education as a Tool for Empowering Women and Achieving Gender Equity - Gusma Afriani; Nurul Zaman (Global Education Journal, 2026)
Education is widely regarded as a strategic instrument for empowering women and advancing gender equity; however, persistent disparities indicate that its transformative potential remains uneven and context-dependent. This study aims to critically examine the extent to which education contributes to women’s empowerment and gender equity by identifying the structural and socio-cultural factors that mediate this relationship. Employing a mixed-methods explanatory sequential design, the research integrates quantitative analysis using structural equation modeling (SEM) with qualitative thematic analysis derived from in-depth interviews. The findings reveal that education has a significant positive effect on women’s agency, economic participation, and decision-making capacity, yet its impact on broader gender equity outcomes is limited by structural barriers such as labor market inequalities and entrenched patriarchal norms. Furthermore, the study highlights that the quality and transformative orientation of education play a more decisive role than mere access or attainment. These results suggest that education functions as a necessary but insufficient condition for achieving gender equity, requiring complementary institutional and socio-cultural reforms. The study contributes theoretically by advancing a non-linear and integrative framework of empowerment, and practically by informing more context-sensitive policy interventions.